Penyuluhan Dan Tata Literasi Keuangan Syariah Pengaturan Keuangan Keluarga Di Kota Ternate Selatan - Rizki Wahyu Utami Ohorella; Sheila Kusumaningrum; Sitti Mukaramah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The importance of knowledge related to Islamic finance and management related to Islamic finance, so that people are not trapped in debt, such as online loans, want financial institutions that provide loans with very large interest to the community. The purpose of this community service is to provide knowledge on the importance of sharia financial literacy and sharia financial management procedures. The method of implementing this community service uses the method; FDG: Lectures, Practices and Participant Assistance. The implementation of this community service was on December 16, 2023, at one of the meeting places in Sasa village, independent PKM activities were held in the afternoon at 13.00 Wit until completion. Participants who attended this PKM activity were 25 people consisting of mothers in Sasa village.